Effects of proteasome inhibitors on cytokines, metalloproteinases and their inhibitors and collagen type-I expression in periprosthetic tissues and fibroblasts from loose arthroplasty endoprostheses. (2nd November 2019) - Niarakis, Anna; Giannopoulou, Eleftheria; Syggelos, Spyros A.; Panagiotopoulos, Elias
ABSTRACT: Objective : Aseptic loosening is a major problem in total joint replacement. Implant wear debris provokes a foreign body host response and activates cells to produce a variety of mediators and ROS, leading to periprosthetic osteolysis. Elevated ROS levels can harm proteasome function. Proteasome inhibitors have been reported to alter the secretory profile of cells involved in inflammation and also to induce ROS production. In this work, we aimed to document the effects of proteasome inhibitors MG-132 and Epoxomicin, on the production of factors involved in aseptic loosening, in periprosthetic tissues and fibroblasts, and investigate the role of proteasome impairment in periprosthetic osteolysis. Materials and methods : IL-6 levels in tissue cultures were determined by sandwich ELISA. MMP-1, -3, -13, -14 and TIMP-1 levels in tissue or cell cultures were determined by indirect ELISA. Results for MMP-1 and TIMP-1 in tissue cultures were confirmed by Western blotting. MMP-2 and MMP-9 levels were determined by gelatin zymography. Gene expression of IL-6, MMP-1, -3, -14, TIMP-1 and collagen type-I was determined by RT-PCR. Results : Results show that proteasome inhibition induces the expression of ΜΜΡ-1, -2, -3, -9 and suppresses that of IL-6, MMP-14, -13, TIMP-1 and collagen type I, enhancing the collagenolytic and gelatinolytic activity already present in periprosthetic tissues, as documented in various studies. Conclusions : These findings suggest that proteasome impairment could be a contributing factor to aseptic loosening. Protection and enhancement of proteasome efficacy could thus be considered as an alternative strategy toward disease treatment.